Near‐Field Energy Transfer between a Luminescent 2D Material and Color Centers in Diamond. Issue 2 (5th November 2019) - Nelz, Richard; Radtke, Mariusz; Slablab, Abdallah; Xu, Zai‐Quan; Kianinia, Mehran; Li, Chi; Bradac, Carlo; Aharonovich, Igor; Neu, Elke
Abstract: Energy transfer between fluorescent probes lies at the heart of many applications ranging from bio‐sensing and bio‐imaging to enhanced photodetection and light harvesting. In this work, Förster resonance energy transfer (FRET) between shallow defects in diamond—nitrogen‐vacancy (NV) centers—and atomically thin, 2D materials—tungsten diselenide (WSe2 )—is studied. By means of fluorescence lifetime imaging, the occurrence of FRET in the WSe2 /NV system is demonstrated. Further, it is shown that in the coupled system, NV centers provide an additional excitation pathway for WSe2 photoluminescence. The results constitute the first step toward the realization of hybrid quantum systems involving single‐crystal diamond and 2D materials that may lead to new strategies for studying and controlling spin transfer phenomena and spin valley physics. Abstract : In this work, Förster resonance energy transfer (FRET) between shallow nitrogen‐vacancy (NV) centers in diamond and atomically thin, 2D tungsten diselenide (WSe2 ) is studied. FRET is detected using fluorescence lifetime imaging, while the NV centers provide an additional excitation pathway for WSe2 photoluminescence. These results may lead to new strategies for studying and controlling spin transfer phenomena and spin valley physics.